2023
DOI: 10.3389/fbioe.2023.1180302
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of AntagomiR-7 through polymer nanoparticles for assisting B Cell to alleviate systemic lupus erythematosus

Abstract: An autoimmune condition known as systemic lupus erythematosus (SLE) is characterized by B cell hyperresponsiveness and persistent generation of pathogenic autoantibodies that cause damage to various organs and tissues. The treatments available today are either ineffective or have adverse effects. The dysregulation of B cell activation is crucial for the emergence of SLE. MiR-7 explicitly targeted PTEN mRNA in B cells. Treatment with antagomiR-7 reduced B cell hyperresponsiveness and prevented the onset of lupu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…These properties have led to PLGA being approved by the FDA for parenteral administration and therefore make it an attractive candidate for nucleic acid delivery 115 . The SA (sialic acid)‐poly (D, L‐lactide‐co‐glycolide) (SA‐PLGA) nano delivery system was used to deliver antagomiR‐7 to splenic B cells 116 . This treatment led to a reduction in B‐cell activity and improvement in lupus nephritis.…”
Section: In Vivo Delivery Vehiclesmentioning
confidence: 99%
See 1 more Smart Citation
“…These properties have led to PLGA being approved by the FDA for parenteral administration and therefore make it an attractive candidate for nucleic acid delivery 115 . The SA (sialic acid)‐poly (D, L‐lactide‐co‐glycolide) (SA‐PLGA) nano delivery system was used to deliver antagomiR‐7 to splenic B cells 116 . This treatment led to a reduction in B‐cell activity and improvement in lupus nephritis.…”
Section: In Vivo Delivery Vehiclesmentioning
confidence: 99%
“…115 The SA (sialic acid)-poly (D, L-lactide-co-glycolide) (SA-PLGA) nano delivery system was used to deliver antagomiR-7 to splenic B cells. 116 This treatment led to a reduction in B-cell activity and improvement in lupus nephritis. This study demonstrated the therapeutic potential of polymeric nanoparticles in targeting specific immune-cell subsets in the context of autoimmune disease.…”
Section: Polymersmentioning
confidence: 99%
“…The therapy reduces immunological abnormalities, restores normal splenic B cell subtypes, and inhibits B cell activation. 220 The delivery of miRNAs via nanoplatforms in inflammatory diseases such as IBD could show promising responses to TNF-α expression. Recently, Louiselle and colleagues, conjugated cerium oxide nanoparticle (CNP)/miRNA-146a embedded chitosan-based gel to target the unregulated inflammatory responses witnessed in IBD/colitis.…”
Section: Mirna Based Targeted Therapeutics In Adsmentioning
confidence: 99%
“…The research findings indicate that SA‐PLGA@antagomiR‐7 possesses favorable biocompatibility and protects antagomiR‐7 against degradation, hence prolonging the presence of the miRNA in the circulatory system in vivo. The therapy reduces immunological abnormalities, restores normal splenic B cell subtypes, and inhibits B cell activation 220 …”
Section: Mirna Based Targeted Therapeutics In Adsmentioning
confidence: 99%